A Porcine Model of Peripheral Nerve Injury Enabling Ultra-Long Regenerative Distances: Surgical Approach, Recovery Kinetics, and Clinical Relevance. Issue 4 (11th May 2020) - Burrell, Justin C; Browne, Kevin D; Dutton, John L; Laimo, Franco A; Das, Suradip; Brown, Daniel P; Roberts, Sanford; Petrov, Dmitriy; Ali, Zarina; Ledebur, Harry C; Rosen, Joseph M; Kaplan, Hilton M; et al.
Abstract: BACKGROUND: Millions of Americans experience residual deficits from traumatic peripheral nerve injury (PNI). Despite advancements in surgical technique, repair typically results in poor functional outcomes due to prolonged periods of denervation resulting from long regenerative distances coupled with slow rates of axonal regeneration. Novel surgical solutions require valid preclinical models that adequately replicate the key challenges of clinical PNI. OBJECTIVE: To develop a preclinical model of PNI in swine that addresses 2 challenging, clinically relevant PNI scenarios: long segmental defects (≥5 cm) and ultra-long regenerative distances (20-27 cm). Thus, we aim to demonstrate that a porcine model of major PNI is suitable as a potential framework to evaluate novel regenerative strategies prior to clinical deployment. METHODS: A 5-cm-long common peroneal nerve or deep peroneal nerve injury was repaired using a saphenous nerve or sural nerve autograft, respectively. Histological and electrophysiological assessments were performed at 9 to 12 mo post repair to evaluate nerve regeneration and functional recovery. Relevant anatomy, surgical approach, and functional/histological outcomes were characterized for both repair techniques. RESULTS: Axons regenerated across the repair zone and were identified in the distal stump. Electrophysiological recordings confirmed these findings and suggested regenerating axons reinnervated target muscles. CONCLUSION: The models presented herein provide opportunities to investigate peripheral nerve regeneration using different nerves tailored for specific mechanisms of interest, such as nerve modality (motor, sensory, and mixed fiber composition), injury length (short/long gap), and total regenerative distance (proximal/distal injury).